Contribution of Cash Waqf Linked Sukuk to the Development of Philanthropy-Based Fintech in Indonesia - Rapida Rapida; Ichsan Abbas; Nurseif Muchtari; Ajrun Ajrun (LPPM UIKA Bogor, 2024)
Cash Waqf Linked Sukuk (CWLS) is a new creative financing product from Indonesia and the first in the world. which provides a blessing impact all the time. The purpose of this writing is to ensure that Cash Waqf Linked Sukuk (CWLS) can make a maximum contribution to the development of philanthropy-based fintech in Indonesia. This type of research is a literature study using a qualitative approach. The data source for this research is secondary data. The data collection method uses literature study, where data is obtained from several references related to the main research theme. The results of this research are that Cash Waqf Linked Sukuk (CWLS ) can make a substantial contribution to the development of the philanthropy-based Financial Technology (Fintech) sector in Indonesia. CWLS's contribution is not only seen in increasing financial efficiency, but also in creating a business model that prioritizes philanthropic values, encouraging fintech development in Indonesia and opening up new opportunities for inclusive and sustainable economic growth.